10-K Filing length and M&A returns. Issue 6 (12th April 2020) - Chircop, Justin; Tarsalewska, Monika
ABSTRACT: This study examines the association between 10-K filing length and M&A returns. We posit that 10-K filing length influences shareholder information acquisition and processing costs. Longer 10-K filings reduce information acquisition costs by making more information about the target available to the shareholder, but may increase information processing costs by increasing the difficulty of extracting that information. Which effect dominates ultimately determines the association between 10-K filing length and M&A returns. We find that 10-K filing length is positively related to M&A returns, suggesting that the reduction in information acquisition costs dominates the increase in information processing costs. This relation is stronger when the acquirer has limited access to private information about the target, and when 10-K filings contain text denoting risk. The relation is weaker when 10-K filings contain complex text and financial statements exhibiting high accounting quality.